KORELASI PENGGUNAAN ALAT PELINDUNG DIRI DENGAN KECELAKAAN KERJA PADA CREW DRILLING - Kasman, Monik (Jurnal Ipteks Terapan, 2016)
Personal Protective Equipment (PPE) is one of the way to control occupational safety and health hazard.Â  PPE is the last risk control to protect workers if control efforts hazard including elimination, substitution of equipment, design, discipline and administration, but the potential risk is still high. This study was purposed to to determine the correlation of using PPE in drilling crew of private (contracted) rig of PT. Pertamina EP Asset Field Jambi which was doing well service to accident in workplace (in the job accident). This study used the cause-effect relationship which there are two variables observed which is influencing variable (independent variable) and affected variable (dependent variable). Subject focused on this study is the total population of 30 drilling crews. The data were analyzed statistically by t-test and correlation test of product moment. Results showed that there is a no strong correlation between wearing PPE and in the job accident. The correlation coefficient of product moment obtained is -0,019, or negative correlation. This negative correlation represents that the relationship between wearing PPE and in the job accident is Â reciprocal, the job accident suffered by drilling crew would be higher by the decreasing of level use of personal protective equipment.